The problem of the status of the Holy Places in Jerusalem and its impact on the Palestinian-Israeli conflict - A. V. Krylov (Международная аналитика)
This article focuses on the legal status of Jerusalem - one of the most complex and debated issues of international law and international politics. Before the establishment of Israel in 1948, over the centuries in the Ottoman period and the years of the British Mandate there was no legally binding bilateral or international treaty that would clearly define the legal status of Jerusalem. However, both the Turkish authorities and the British administration in Palestine preceding from the fact that Jerusalem is the center of three world religions, fully ensured of the rights of believers of all confessions. In accordance with the well-known international instruments of law all Jerusalem should be a special territory of Corpus Separatum, which will be subjected to the international control (UN General Assembly Resolution 181 / II of 29 November 1947). However, in 1980 the Israeli Parliament declared Jerusalem the «eternal and undivided capital» of Israel, including the Arab territories of East Jerusalem occupied in 1967. This law, as well as the Israeli law on the protection of the Holy Places has radically changed the Status quo which existed for centuries. No country in the world recognizes Israel’s attempts to change the legal Status of the City. In the present article the following aspects are analyzed: • The Status of the Holy Places in Jerusalem, before the establishment of the British mandate over Palestine in 1922; • The Status of the Holy Places in Jerusalem in accordance with the international law instruments; • The Status of the Holy Places in Jerusalem after the partition of the City on the Israeli and Jordanian enclaves in 1948; • Change of the Status of the Holy Places of Jerusalem after the June 1967 War and the impact of this transformation both on the Arab-Israeli and the Palestinian-Israeli conflicts; • Actions taken by Israel to change the Status of the Temple Mount; • The problem of the Status of Jerusalem in the Palestinian-Israeli Peace Process.